The Diagnostic Journey of Dysautonomia Patients: Insights from a Patient-Reported Outcome Study - John A. O’Dell MSN, MBA; Ash Walker DHSc; Andrew J. Latham PhD; Daniel J. Parisian PhD; Lindsay E. Branch BS; Dreena D. Vanderburg; Ava A. Cox; Shelley Chavis; Silvia E. Smith PhD (Journal of Patient Experience)
Dysautonomia refers to any disorder involving altered function of the autonomic nervous system. Dysautonomia can be debilitating as it often affects multiple organ systems. The diagnostic journey for individuals affected by dysautonomia can be hindered by symptom overlap with other conditions and by limited access to autonomic specialists. The present patient-reported outcome study aims to characterize the diagnostic journey of 672 adult individuals affected by different types of dysautonomia. The average time to diagnosis was 7.7 years (SD 10 years) and diagnosis was made primarily by cardiologists, followed by neurologists, and internists or primary care physicians. Common comorbid conditions are Ehlers-Danlos syndrome, mast cell disorders, vitamin deficiency, fibromyalgia, and myalgic encephalomyelitis, all of which can contribute to the symptoms burden and can potentially confound the diagnostic process. We suggest that the prolonged time to diagnosis contributes to morbidity and compounds the psychological and economic burden of dysautonomia. Raising awareness about the numerous obstacles that hinder the diagnostic process among both clinicians and dysautonomia patients is the first step to reduce morbidity and improve clinical outcomes.